Heterogeneous firms and the micro origins of aggregate fluctuations - Glenn Magerman; Karolien De Bruyne; Emmanuel Dhyne; Jan Van Hove (National Bank of Belgium, 2016)
This paper evaluates the impact of idiosyncratic productivity shocks to individual firms on aggregate output. Two sources of firm-level heterogeneity contribute to aggregate fluctuations: (i) asymmetries in supplier-buyer relationships and (ii) the skewed distribution of sales to final demand. We first develop a model with monopolistic competitive firms and derive a generalized centrality measure that takes these two sources of heterogeneity into account. The model is subsequently estimated using unique data on firm-to-firm transactions across all economic activities in Belgium. The model generates aggregate volatility from micro origins in the same order of magnitude as observed volatility in GDP. The top 100 firms contribute to 90% of the volatility generated by the model, underlining a strong granularity of the economy. Counterfactual analysis further shows that both sources of micro heterogeneity contribute substantially to aggregate fluctuations, while the relative contribution of each channel crucially depends on the labor share in the economy.
Keywords: E3; L1; 330; Heterogeneous firms; networks; input-output linkages; aggregate volatility; Monopolistischer Wettbewerb; Unternehmensnetzwerk; Volatilität